Women's Spiritual Leadership in Africa : Tempered Radicals and Critical Servant Leaders - Ngunjiri, Faith Wambura, 1973- (Book collections on Project MUSE., 2010)
"Women's Spiritual Leadership in Africa offers portraits of sixteen African women in leadership positions in grassroots, national, Pan African and global organizations, and explores how they choose to "rock the boat without falling out" by transforming their communities and organizations from within. In her analysis of the women leaders' experiences, Faith Wambura Ngunjiri demonstrates how these African women navigate cultural and organizational challenges, including the intersecting oppressions of gender, ethnicity, class, and marital status, in order to act boldly against social and economic injustices. Ngunjiri characterizes the women as "critical servant leaders" because of their approach to leadership, where they lead through service while deconstructing patriarchal social and institutional practices and providing positive alternatives. The women's tempered radicalism and servant leadership is deeply informed by African and Christian spirituality, which animates and informs their lives and leadership experiences. Collectively, the women's stories present an important and inspiring vision of contemporary women's leadership in African contexts."--BOOK JACKET.